Service Operations Mastery: A Holistic Toolset for Achieving Operational Excellence and Service Superiority - Firdaus Abdullah; Nini Hartini Asnawi; Abg Hamizam Abg Mohara (Information Management and Business Review, 2023)
Effective operations management is central to achieving superior operational performance, whether in the manufacturing or service sector. While many studies have examined the importance of operations in manufacturing, less attention has been given to service operations management, particularly from the perspective of service operations managers. This study aims to bridge this gap by developing a comprehensive instrument for service operations management. By combining qualitative and quantitative approaches, we identified six key elements that underpin service operations management: Equipment Management, Human Initiatives, Service Delivery Control (SDC), Certifications, Technology Usage, and Service Delivery Design (SDD). Confirmatory factor analysis (CFA) confirmed the one-dimensionality of these factors, demonstrating their close interconnection. The instrument exhibited strong reliability and validity, enabling it to provide a structured framework for the empirical understanding of operations management in the service sector.